Inovasi Produk Herbal Telang Panjare Untuk Peluang Usaha Warga Kelurahan Gunung Anyar - Yudha, Tengku Sandi Yudha; Soebiantoro, Ugy (Abimanyu : Jornal of Community Engagement, 2024)
The butterfly flower, usually call the Telang flower, is a type of plant that grows like beans and has purple leaves. Butterfly pea flowers contain anthocyanin compounds, so when used as a solvent, they produce a purple color in food products. The anthocyanin compounds used as natural dyes also have antioxidant properties, which function to ward off free radicals and prevent premature aging and degenerative diseases. In this activity, the community RW1 Gunung Anyar Village, especially the KSH Cadres, were accompanied and given counseling regarding the manufacture and benefits of Telang Panjare Syrup, which can be used as a business opportunity by developing innovative products that can increase the sales value of consumer herbal drinks and create new market share so that this product can become a sustainable business. Panjare Telang Syrup is a beverage product made from herbal ingredients made from Telang flowers, which have a characteristic blue color. Also, the blue color dissolves in water, so the packaging looks attractive. UPN's "veteran" East Java village development team saw a business opportunity and experimented with producing Terang He Panjare His syrup. This idea was finally implemented well in socialization activities with the theme "Business Management Strategies for MSMEs."